Recent advances in the diagnosis and management of pre-eclampsia - Duhig, Kate E. (F1000Prime Rep, 2015)
Pre-eclampsia complicates around 5% of pregnancies and hypertensive disorders of pregnancy are responsible for over 60,000 maternal deaths worldwide annually. Pre-eclampsia is characterized by hypertension and features of multiple organ disease. Diagnosis remains a challenge as clinical presentation is highly variable and even with severe disease a woman can be asymptomatic. Pre-eclampsia is characterized by abnormal placentation with subsequent maternal inflammatory and vascular response. Improved understanding of the underlying pathophysiology relating to the role of angiogenic factors, has emerged and placed intense interest on their role in prognostic modelling or diagnosis of pre-eclampsia. This article summarizes new developments in diagnosis with a focus on angiogenic biomarkers for prediction of disease onset, and recent advances in management strategies for patients with pre-eclampsia.